Comprehensive management of vulvovaginal cancers - Angélica Nogueira‐Rodrigues; Maaike H. M. Oonk; Domenica Lorusso; Brian Slomovitz; Mario M. Leitão; Glauco Baiocchi (CA: A Cancer Journal for Clinicians, 2025)
AbstractVulvar and vaginal cancers represent rare malignancies, with an incidence of 2.7 per 100,000 women for vulvar cancer, predominantly affecting women older than 60 years, although rising rates are observed in younger demographics. Approximately 90% of vulvar cancers are squamous cell carcinoma and frequently are associated with human papillomavirus (HPV) infection. Vaginal cancer, constituting less than 1% of all female cancers, similarly exhibit HPV‐related trends. This review delineates the etiology, histopathology, and treatment strategies for carcinomas and vulvovaginal melanomas and sarcomas. Surgical intervention remains the primary treatment modality for vulvar cancer, involving tumor resection and inguinofemoral lymph node staging. For locally advanced vulvar carcinoma, chemoradiation is advised when exenterative surgery would be indicated. Recurrence rates within 2 years after diagnosis range from 12% to 37%. Unfortunately, systemic treatments for recurrent or metastatic disease are limited, with 5‐year survival rates at approximately 20%. Current evidence primarily derives from retrospective studies or small phase 2 trials or otherwise is extrapolated from the treatment of cervical cancer. Enrollment in clinical trials is strongly advocated, along with prompt access to best supportive care to mitigate the effect of locoregional progression on quality of life. Moreover, the psychosocial implications of treatment on body image and sexuality necessitate careful consideration. Future HPV vaccination initiatives may reduce cancer incidence, although significant effects of such vaccination will manifest over decades, underscoring the urgent need to enhance treatment efficacy and minimize morbidity in vulvar and vaginal cancers.